Follow‐Up Magnetic Resonance Imaging in Monitoring Charcot Foot and Its Association With Total Contact Cast Treatment Duration and Long‐Term Outcomes: A Retrospective Cohort Study - Johan Schoug; Per Katzman; Erik Uddman; Magnus Löndahl (Journal of Foot and Ankle Research)
ABSTRACT Aims/Hypothesis Charcot foot (CF), a potentially debilitating complication of neuropathy, requires offloading to avoid foot deformities. Follow‐up MRI examinations are often used to determine the optimal duration of total contact cast (TCC) offloading treatment. This study investigated the use of follow‐up MRI during CF treatment and its relationship to offloading duration and risk of future surgery. Methods People with diabetes mellitus and MRI‐confirmed CF treated at Skåne University Hospital (Lund and Malmö, Sweden) between 2006 and 2022 were studied retrospectively. Individuals monitored with follow‐up MRI examinations were compared with those who only underwent diagnostic MRI. A regression model was applied to evaluate factors predicting TCC and total CF treatment duration. Results One‐hundred and twenty‐two individuals (45 [37%] DM1; 47 [39%] women; median age 60 [IQR 53–68] years) with a total of 143 CF events were included. 76 (53%) of these CF events were monitored using a total of 141 follow‐up MRI examinations. Individuals monitored with MRI had significantly longer TCC and total CF treatment durations (p < 0.001). Individual characteristics (with the exception of sex), rate of stage 1 CF, and risk of future surgery did not differ between the two groups and only use of follow‐up MRI (p < 0.001) remained a significant predictor of both longer TCC and total CF treatment durations in a regression model. Conclusions/Interpretation In this retrospective cohort study, use of follow‐up MRI was associated with longer TCC and total treatment times despite similar characteristics and outcomes. Prospective studies are needed to further elucidate the optimal use of MRI in monitoring CF.